2013
DOI: 10.2466/17.21.pr0.113x14z6
|View full text |Cite
|
Sign up to set email alerts
|

Responding to Moral Dilemmas: The Roles of Empathy and Collectivist Values among the Chinese

Abstract: The present study assessed how empathy and vertical collectivism are related to moral competency in a sample of Hong Kong Chinese university students (N = 153; 70 men, 83 women). The Emotional Tendency Scale, Individualism-Collectivism Scale, and Moral Judgment Test were used to quantify empathy, vertical collectivism, and moral competency, respectively. Results showed that empathy was not statistically significantly correlated with moral judgment. The interaction of vertical collectivism and empathy predicted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 25 publications
0
6
0
1
Order By: Relevance
“…For example, Stipek () found that people in individualist cultures are more likely to experience pride in response to personal accomplishments, while people in collectivist cultures are more likely to experience pride in response to successes that benefit others. In contrast, Mann and Cheng () argue that unlike those in individualist cultures, people in collectivist cultures tend to display an inclination to place the interests of the collective above their own when they experience empathy.…”
Section: Studymentioning
confidence: 97%
“…For example, Stipek () found that people in individualist cultures are more likely to experience pride in response to personal accomplishments, while people in collectivist cultures are more likely to experience pride in response to successes that benefit others. In contrast, Mann and Cheng () argue that unlike those in individualist cultures, people in collectivist cultures tend to display an inclination to place the interests of the collective above their own when they experience empathy.…”
Section: Studymentioning
confidence: 97%
“…With public officials in Korean public sectors as the object of investigation, a positive correlation exists between social capital and knowledge sharing (Kim, 2018). The higher the tacit knowledge, the stronger the knowledge sharing of the collectivist-oriented people (Yu, 2014), Zhong-yong is the representative of Confucian culture and reflects the value of Chinese collectivism (Mann and Cheng, 2013). Knowledge sharing positively moderates the relationship between core self-evaluation and creativity (Mittal, 2015).…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%
“…For decision making, Briley, Morris and Simonson () found that Hong Kong students tended to avoid losses when the decision task was presented in Chinese ( vs English), complying with the prevention focus strategy of the motivational approach in Chinese culture. For decision making in the realm of morality, Mann and Cheng () examined the inter‐relationship among cultural values, empathy and moral competence in Hong Kong bilingual students. They focused on participants' moral competence instead of their judgements of moral dilemmas and found that empathy interacted with the degree of collectivism in predicting moral competence.…”
Section: The ‘Language Effect’ On Moral Judgementmentioning
confidence: 99%